2019
DOI: 10.3390/cancers12010094
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of FAK Expression on the Cytotoxic Effects of CIK Therapy in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is a special subtype of breast cancer in which several common diagnostic biomarkers are lost. Due to the loss of expression of receptors, treatment options for TNBC are limited. Therefore, finding safe and effective treatments for patients with TNBC is a major objective for clinicians. Previous studies suggested that cytokine-induced killer (CIK) cells may be beneficial for patients with a variety of tumor types. However, CIK therapy is not effective for all patients. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 60 publications
0
22
1
Order By: Relevance
“…Of note, FAK over-expression has been tightly correlated with the malignant grade [66] as well as the poor clinical outcome in TNBC patients [22]. Moreover, FAK activation was involved in the peculiar features of TNBC [65], whereas the inhibition of FAK signaling prevented the metastatic potential of TNBC cells [22,23] and enhanced the sensitization to anti-cancer treatments [67]. However, the precise mechanism by which FAK acts in TNBC are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, FAK over-expression has been tightly correlated with the malignant grade [66] as well as the poor clinical outcome in TNBC patients [22]. Moreover, FAK activation was involved in the peculiar features of TNBC [65], whereas the inhibition of FAK signaling prevented the metastatic potential of TNBC cells [22,23] and enhanced the sensitization to anti-cancer treatments [67]. However, the precise mechanism by which FAK acts in TNBC are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that, while not affecting primary tumor development and growth, FAK deletion significantly suppressed breast cancer metastasis in vivo [ 40 ]. Another study demonstrated that knockdown of FAK expression in TNBC cells or the treatment of TNBC cells with a FAK inhibitor followed by co-culture with cytokine-induced killer (CIK) cells increased the death of TNBC cells, suggesting that FAK plays an important role in sensitizing tumor cells to CIK cells [ 41 ]. Interestingly, our results supported the most recent study, which demonstrated that inhibition of FAK enhanced 5-FU chemosensitivity to gastric carcinoma [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It experiment process is displayed in Fig.1a. After excluding the drugs that had been reported to be related to PD-L1, such as the inhibitors of MEK [27][28][29] , FAK [30][31][32][33][34] and ALK [35][36][37] , we found that amlodipine, a dihydropyridine calcium channel blocker 38 , abundantly decreased the expression of PD-L1 in cancer cells ( Supplementary Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%